2021
DOI: 10.1182/blood.2020006892
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase 2 trial of pomalidomide in subjects failing prior therapy for chronic graft-versus-host disease

Abstract: Steroid-refractory chronic graft-versus-host disease (cGvHD) is a therapeutic challenge. Sclerotic skin manifestations are especially difficult to treat. We conducted a randomized phase-2 clinical trial to determine safety, efficacy, and preferred dose of pomalidomide in persons with moderate to severe cGvHD unresponsive to corticosteroids and/or subsequent lines of therapy. Thirty-four subjects were randomized to receive pomalidomide, 0.5 mg/d; LD) orally (n=17) or 2 mg/d at a starting dose of 0.5 mg/d increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Pomalidomide is a thalidomide derivative with 4,000-fold greater inhibition of TNF-alpha, which was originally used in the treatment of multiple myeloma. It has been evaluated in several adult studies for the treatment of SR-cGvHD with 54-67% ORR observed (201,202). Paediatric data are lacking.…”
Section: New and Emerging Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pomalidomide is a thalidomide derivative with 4,000-fold greater inhibition of TNF-alpha, which was originally used in the treatment of multiple myeloma. It has been evaluated in several adult studies for the treatment of SR-cGvHD with 54-67% ORR observed (201,202). Paediatric data are lacking.…”
Section: New and Emerging Therapiesmentioning
confidence: 99%
“…Of note, single-target inhibitors may have a beneficial or detrimental effect at different phases of immune cell development and immune dysfunction. In this regard the results of a randomised phase 2 trial evaluating the response of pomalidomide in 34 adult patients with moderate to severe cGvHD may serve as an example: authors reported that the use of pomalidomide early after HSCT may cause cutaneous inflammation in contrast to the treatment responses observed in late sclerotic cGvHD (201).…”
Section: Personalised Management Of Paediatric Cgvhdmentioning
confidence: 99%
“…In another phase III trial, on the basis of BTZ and dexamethasone, pomalidomide was added in the treatment of patients with RRMM to significantly improve PFS (11.20 vs. 7.10 months; HR, 0.61; 95%CI, 0·49–0.77; p < 0·0001), with acceptable hemocyte toxicity (NCT01734928) ( Richardson et al, 2019 ). In addition to malignancy, pomalidomide is a well-tolerated and efficient treatment for advanced steroid-refractory chronic graft-versus-host disease (cGVHD), indicating the antifibrotic effects of pomalidomide are related to the increased levels of blood regulatory T cells and IL-2 (NCT01688466) ( Curtis et al, 2021 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Therefore, when using IMiDs after allo-HSCT, it is necessary to pay attention to the onset of GVHD, and it may be important to measure cytokines over time and/or analyze lymphocyte subsets. Although IMiDs may also be a treatment option for chronic GVHD 11 , chronic GVHD differs from acute GVHD in the cells, and the mechanisms involved and onset and severity of GVHD might be different depending on the timing of administration and dose.…”
Section: Figure 2 Clinical Coursementioning
confidence: 99%